2004
DOI: 10.2320/matertrans.45.1794
|View full text |Cite
|
Sign up to set email alerts
|

Study of Micro-Droplet Behavior for a Piezoelectric Inkjet Printing Device Using a Single Pulse Voltage Pattern

Abstract: The aim of this study is to investigate the formation and ejection behavior of droplets created by a squeeze mode piezoelectric inkjet printing device using a single pulse voltage pattern. The test liquids are de-ionized (DI) water and ethylene glycol. The experimental results and acoustic wave theory are used to discuss the effects of operating frequency, positive voltage keeping time and pulse voltage magnitude on the volume and velocity of the droplets. For this study, a squeeze mode piezoelectric printhead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…It has been experimentally observed that the drop formation process and ejected drop characteristics strongly depend on the pulse characteristics [ 11 , 13 , 14 ]. Short t rise and t fall times, in the order of few microseconds, are needed to have jet formation.…”
Section: The Physics Of Inkjet Printing: Drop Formation Depositiomentioning
confidence: 99%
“…It has been experimentally observed that the drop formation process and ejected drop characteristics strongly depend on the pulse characteristics [ 11 , 13 , 14 ]. Short t rise and t fall times, in the order of few microseconds, are needed to have jet formation.…”
Section: The Physics Of Inkjet Printing: Drop Formation Depositiomentioning
confidence: 99%
“…Hence, the trailing thread disintegrated from the liquid column with a lower velocity than the main droplet becomes a satellite droplet in some cases. 9) Within the workable voltage range, three different conditions are observed. The first case is that single droplet can be generated and ejected for each cycle of the waveform, which is the most desirable condition of the DOD inkjet printing process.…”
Section: Observation Of Dropletsmentioning
confidence: 99%
“…If this positive pressure wave has enough energy, it will eject a droplet. 9) In earlier studies, the time evolution of the liquid shape, which includes ejected liquid from nozzle to form liquid column, necking of liquid column, variations of liquid column, and formation as well as combination of main droplet and satellites, has been observed during the formation and ejection of the droplet. 7,10) At early stage of ejection, the contracted transducer expands; liquid in the nozzle is accelerated and pushed out of the nozzle orifice.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental cell boundaries segment after advection segment before advection observation of the droplet ejection behaviors caused by a single or a double voltage pulse is successfully explained through the propagation of acoustic pressure waves. 25,26) During positive pressure period, the meniscus at the nozzle exit is formed and then a jet is created. The ejected liquid is separated from nozzle when the negative pressure is applied.…”
Section: Resultsmentioning
confidence: 99%